Fine Possibilities of Decorative Traditional Popular Clothing in Asir Region and its role in Contemporary Technical Artifacts Production - Al-Qahtani, Razan Abdullah (Journal of Educational and Psychological Sciences, 2018)
This research was aimed to design contemporary technical artifacts derived from Asir’s folk costume and identify formulations fine decorations popular women’s clothing in Asir region (Almjunb dress), and implementation of contemporary technical artifacts art derived from Asir’s folk costume. The researcher followed in this research a descriptive analytical method and experimental method. the experimental used in the decomposition of the formulations fine decorations for the popular women’s clothing in Asir region (Almjunb dress), then designed and implemented contemporary technical artifacts derived from Asir’s folk costume. The results showed that traditional popular clothing in asir region contains several geometric, botanical and symbolic decorations, and the most popular female clothing in asir region (almjunb dress) contains wild variety of colors (black, white, red, orange, yellow, blue and green), also, the research emphasized on the importance of fine possibilities of decorative traditional popular clothing in asir region and its role in contemporary technical artifacts production. The research recommended that official in Saudi Arabia should design a website which contains heritage clothing photos in the kingdom.
Keywords: plastic capabilities; decorations; folk clothes; artifacts